2018
DOI: 10.1007/s12035-018-1058-0
|View full text |Cite
|
Sign up to set email alerts
|

SIRT2 Inhibition Confers Neuroprotection by Downregulation of FOXO3a and MAPK Signaling Pathways in Ischemic Stroke

Abstract: Sirtuin 2 (SIRT2) is a family member of nicotinamide adenine dinucleotide (NAD)-dependent deacetylases which appears to have detrimental roles in an array of neurological disorders such as Parkinson's disease (PD) and Huntington's disease (HD). In light of the recently emerging roles of sirtuins in normal physiology and pathological conditions such as ischemic stroke, we investigated the role of SIRT2 in ischemic stroke-induced neuronal cell death. Primary cortical neurons were subjected to oxygen-glucose depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 54 publications
3
46
0
1
Order By: Relevance
“…They are involved in various cellular physiological processes, such as energy metabolism, oxidative stress, and apoptosis. Their ability to resist oxidative stress has been widely studied in cerebral ischemia-reperfusion (Hou et al, 2010;Rothgiesser et al, 2010;Morris et al, 2011;She et al, 2018;Wang et al, 2018;Wu D. et al, 2018;Chang et al, 2019;Duan et al, 2019;Fusco et al, 2019;Rao et al, 2019;Xian et al, 2019;Zhao B. et al, 2019). SIRT1 activates the FOXO family, and FOXO3a has the ability to resist anti-oxidative stress and enhances ROS scavenging activity (Hou et al, 2010).…”
Section: Sirt/foxo Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…They are involved in various cellular physiological processes, such as energy metabolism, oxidative stress, and apoptosis. Their ability to resist oxidative stress has been widely studied in cerebral ischemia-reperfusion (Hou et al, 2010;Rothgiesser et al, 2010;Morris et al, 2011;She et al, 2018;Wang et al, 2018;Wu D. et al, 2018;Chang et al, 2019;Duan et al, 2019;Fusco et al, 2019;Rao et al, 2019;Xian et al, 2019;Zhao B. et al, 2019). SIRT1 activates the FOXO family, and FOXO3a has the ability to resist anti-oxidative stress and enhances ROS scavenging activity (Hou et al, 2010).…”
Section: Sirt/foxo Signaling Pathwaymentioning
confidence: 99%
“…Inflammatory cytokines can enhance the activity of SIRT2 in cells, enhance its deacetylation of NF-κB, reduce the transcriptional activity of NF-κB, and reduce the expression of inflammatory mediators, such as interleukin-6 (IL-6), matrix metalloproteinase 9 (MMP9), and cyclooxygenase-2 (COX-2), to exert antioxidant and anti-inflammatory effects (Rothgiesser et al, 2010). Further studies have also shown that SIRT2specific activity inhibitor can aggravate neurological impairment after CIRI, and identified the downregulation of AKT/FOXO3a and p38/MAPK pathways as intermediary mechanisms that may contribute to the reduction in apoptotic cell death caused by SIRT2 inhibition (She et al, 2018;Wu D. et al, 2018). SIRT3 enhances SOD2 activity by deacetylating its lysine residues, reducing ROS levels in cells or tissues, increasing the organism's ability to resist oxidative stress, and inhibiting apoptosis (Wang et al, 2018).…”
Section: Sirt/foxo Signaling Pathwaymentioning
confidence: 99%
“…SIRT1, SIRT2, and SIRT3 have the highest deacetylase activities and can exert great neuroprotective effects in cerebral ischemia [ 60 62 ]. With an NAD+-dependent deacetylase, SIRT1, SIRT2, and SIRT3 specifically promote the transcription of a set of genes related to cell survival [ 63 65 ], mitochondrial function [ 66 ], energy metabolism [ 26 , 66 , 67 ], oxidizing reaction [ 65 , 66 , 68 ], and inflammation [ 69 , 70 ]. SIRT1/2/3 deficiency or knockdown attenuated the neuroprotection of NAD+ [ 52 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 and SIRT2 are key regulators of cellular antioxidative and antiapoptotic responses [ 26 , 71 , 72 ], and similar to SIRT1/2, NRF2 plays a crucial role in promoting mitochondrial biogenesis and regulating mitochondrial function with a relatively independent manner [ 43 , 58 , 73 ]. Under cellular stresses, SIRT1/2 can deacetylate FOXO1 and FOXO3A [ 68 , 72 , 74 ], and the transcriptional activity mediated by NRF2 is improved, which in turn, induces the increase of antioxidant genes expression, decrease of ROS production, and upregulation of mitochondrial superoxide dismutase (MnSOD) expression [ 58 , 68 ]. In this study, OGD/R induction led to the SIRT1/2 downregulation, decrease of FOXO3a nuclear localization and phosphorylated levels (Figures 5(e) – 5(g) ), increase of the ROS production, downregulation of antioxidant proteins and factors (SOD, CAT, MnSOD), and mitochondria injury (Figures 5(e) – 5(g) ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation